Pet strategij proti nedovoljenim posegom v prostor - Mušič, Vladimir Braco (Teorija in praksa, 1993)
Author joined the recent polemics on problems of illegal construction, starting with the case of Mali Vrhek near Ljubljana, and stands for a more profound research of related problems. M. Vrhek ought to be seen within broader dimensions of obstinate encroachments upon space, for these menace the natural and manmade values of the human environment. Early warnings in the architectural publications of the 50's in subsequent research reports and societal actions are mentioned. The main part of the contribution analyzes 5 strategies, esential for an efficient implementation of any environmental preservation and design policies, i.e. legislation, financial obligations, proper technical solutions, education, and community participation. One of the problems in concerning this has been improper land economics, but there is also a reflectin of basic contradictions in the development of Slovenia, as well as up to now poorly prepared administrative measures.
Keywords: prostorsko urejanje; urbanism; urbanizem; Slovenia; Slovenija; Mali Vrhek; črne gradnje; zakonodaja